DIPG-39. New preclinical models for Diffuse Midline Glioma. (3rd June 2022) - Klenner, Marbod; Freidel, Pia; Filbin, Mariella G; Beck, Alexander
Abstract: Malignant brain tumors are the leading cause of childhood death in Germany, with Diffuse Midline Glioma (DMG) being the most lethal of all paediatric brain tumors. Current treatment strategies are limited to irradiation which prolongs survival only by a few months. Preclinical studies have identified effective drug candidates, but translation into the clinic remains a major obstacle. It is known that interactions between tumor cells and components of the TME (tumor microenvironment), such as cell to cell contacts between malignant and non-malignant cells or secreted factors, can increase therapy resistance and progression of brain tumors. However, these important factors are not present in most conventional cell culture models for drug testing. Consequently, there is a need for more realistic DMG models to improve the relevance and translational potential of current drug screening. Therefore, the goal of this study was to develop a new DMG model for drug testing, consisting of induced pluripotent stem cell (iPSC) derived human brain cells and patient derived DMG cells to better mimic the complex tumor microenvironment. We co-cultured three-dimensional cerebral organoids with DMG tumor spheres resulting in the formation of DMG-Brain-Organoids (DBO). Preliminary results show that co-culture induces distinct tumor cell subpopulations corresponding to those detected in DMG tumors by single cell RNA sequencing (Filbin et al., 2018). These subpopulations mainly differ in their proliferative capacity and their differential response to clinical interventions may be critical for therapeutic success. DBOs subjected to drug treatments (single or combination) were sectioned and individual therapy effects on tumor cell subpopulations and proliferative capacity were monitored using multiplexed immunofluorescence imaging. By observing drug effects in a realistic setup, we hope to improve the predictive power of our preclinical drug screens and to find new combination therapies for DMG.